Company Name: Secret Recipe - Thinnosha A/P Thambyraja; Daisy Mui Hung Kee; Patmapriya A/P Morali; Thaneshweri A/P Thangesvaren; Vejaydarssni A/P Pushpagaran; Abdulmohsen Alnassar (International Journal of Tourism and Hospitality in Asia Pasific, 2019)
Secret Recipe has launched its market to several countries such as Singapore, Indonesia, Thailand, Philippines, and China and all over Malaysia. It expects its market will launched internationally in the future. Secret Recipe has earned numerous accolades every year; some of the more prominent ones are * Best Cheesecake Award 1998 * Most Original Chocolate Award 1999 * Best Cheesecake Award 2000 * Best Lamb Stew Award 2001 * Enterprise 50 Award 2002 b. Vision .The purpose of this project is to analyse the issues facing by the company and give some suggestions to overcome the problem,enhance learning in organisational behaviour and by joining this project student can learn other cultures.The methods that we are going to use to complete this research are by interviewing which enable face to face discussion,brainstorming by having discussion in group to solve the issues,survey,online research method to get more information such as company’s history and company’s oraganisation,questionnaire. Based on the research the issues faced by Secret Recipe Company are financial management process,employee problems,increase in price of the product due to raw materials scarcity and hight cost production ,competition,and weakness in internal control(human resource). Based on this project we can conclude that this project can be a new and effective way and solution for the companies that are facing issues in their business.We also get an opportunity to work as a consultant and get experience in providing solution for companies in Asia.Through this project we have learnt and gain knowledge and expand our networking.